THE ROLE OF SOCIAL COMMERCE CONSTRUCTS, SOCIAL SUPPORT, AND TRUST IN COMMUNITY ON SOCIAL COMMERCE ACTIVITIES - Amir Hidayatulloh (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2018)
This study aims to analyze social commerce constructs, social support, and individual trust in the community in social commerce activities. Social support includes emotional support and informational support. The population was social media users, while the samples were social media users who had made purchase at least two transactions through social media. The sampling technique was convenience sampling. Totally, 162 respondents were involved. Hypothesis testing was done using Warp PLS. This study reveals that individual trust in the community can be built directly through the social commerce constructs. These constructs affects both emotional support and information support, in which they will ultimately affect the individual trust in the community. Furthermore, social commerce intention is influenced by individual trust in the community and emotional support. However, information support does not affect the social commerce intention.